2018
DOI: 10.1111/birt.12345
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding in hospital predicts longer breastfeeding duration in Canada: Implications for health equity

Abstract: Exclusive breastfeeding in hospital is associated with longer breastfeeding duration, particularly among women of lower socioeconomic status. Initiatives that support exclusive breastfeeding of newborns in hospital could improve long-term breastfeeding rates and help reduce health inequities arising in early life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 30 publications
6
49
3
2
Order By: Relevance
“…According to previous studies that evaluated some of the practices examined here, breastfeeding in the first hour of life, no supplementation with infant formula, and no pacifier use were the practices most strongly associated with longer breastfeeding duration (DiGirolamo, Grummer‐Strawn, & Fein, ). A recent study conducted in Canada also showed that babies who were breastfed exclusively during their stay in the maternity ward were breastfed for longer when compared with those who received formula (median: 11 vs. 7 months; Vehling et al, ), corroborating the findings of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…According to previous studies that evaluated some of the practices examined here, breastfeeding in the first hour of life, no supplementation with infant formula, and no pacifier use were the practices most strongly associated with longer breastfeeding duration (DiGirolamo, Grummer‐Strawn, & Fein, ). A recent study conducted in Canada also showed that babies who were breastfed exclusively during their stay in the maternity ward were breastfed for longer when compared with those who received formula (median: 11 vs. 7 months; Vehling et al, ), corroborating the findings of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Providing an infant with anything other than breast milk in the first few days after birth (prelacteal feeding) is associated with delayed initiation of breastfeeding (Grassley, Schleis, Bennett, Chapman, & Lind, ; Sharma & Byrne, ) and increases risk of pathogenic infection and diarrheal disease (Debes et al, ; Ogbo, Page, Idoko, Claudio, & Agho, ). In‐hospital breast milk substitute (BMS) supplementation during this period has a negative impact on later exclusive and continued breastfeeding (Chantry, Dewey, Peerson, Wagner, & Nommsen‐Rivers, ; T. T. Nguyen, Withers, Hajeebhoy, & Frongillo, ; Vehling et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In-hospital breast milk substitute (BMS) supplementation during this period has a negative impact on later exclusive and continued breastfeeding (Chantry, Dewey, Peerson, Wagner, & Nommsen-Rivers, 2014;T. T. Nguyen, Withers, Hajeebhoy, & Frongillo, 2016;Vehling et al, 2018).…”
mentioning
confidence: 99%
“…Avoiding exposure to pacifiers or artificial nipples while inpatient (Step 9) increased the likelihood of any breastfeeding by a factor of 5.7, while avoiding inpatient formula supplementation (Step 6) increased the likelihood of exclusive breastfeeding by 4.4 times in the early postpartum period. Avoiding inpatient formula supplementation for nonmedical reasons has been associated with longer exclusive and partial breastfeeding duration in the literature . However, others found no effect of formula supplementation on breastfeeding outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…Avoiding inpatient formula supplementation for nonmedical reasons has been associated with longer exclusive and partial breastfeeding duration in the literature. [11][12][13][14][25][26][27] However, others found no effect of formula supplementation on breastfeeding outcomes. [28][29][30] It is hypothesized that formula supplementation may interfere with the physiology of milk production because of an interruption of the natural balance between supply and demand.…”
Section: Discussionmentioning
confidence: 99%